The Effect of Problem Based Learning Model on Improving Mathematical Critical Thinking Abilities and Students' Learning Independence at MAN 1 Medan, Indonesia - Siregar, Ahmad Rifai; Hasratuddin, Hasratuddin; Rangkuti, Yulita Molliq; Londong, Ahmad; Siregar, Julya Syahleni; Siregar, Fadhillah Rahma (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
This study investigated the effectiveness of Problem Based Learning (PBL) compared to the Traditional Learning Model in mathematics education, focusing on two key aspects: students' mathematical critical thinking skills and learning independence. The research examined whether PBL yielded better results than traditional methods in enhancing these capabilities, while also analyzing potential interactions between learning approaches and students' initial mathematical abilities. The study was conducted with a sample of 60 tenth-grade students from MAN 1 Medan, drawn from classes X-9 and X-6, who were divided into experimental and control groups. Using mathematical critical thinking skills assessments and a learning independence scale, data were analyzed through two-way ANOVA. The results demonstrated that the PBL model was significantly more effective than the Traditional Learning Model in improving both students' mathematical critical thinking skills and learning independence. However, no significant interactions were found between learning approaches and students' initial mathematical abilities in either the development of critical thinking skills or learning independence. These findings strongly suggest that Problem Based Learning should be considered as an effective instructional strategy for educators seeking to enhance their students' mathematical critical thinking skills and foster greater learning independence in the classroom.